Comparative analysis of preparation errors and contamination in robotic and manual chemotherapy compounding: A systematic review and meta-analysis - Kaewbut, Piranee; Samprasit, Nathapol; Saepoo, Sarocha; Arsu, Aimusa; Rattanatanyapat, Pitchayut (Journal of Medicine and Health Sciences, 2025)
The number of cancer patients in Thailand has been steadily increasing, leading to a significant rise in the demand for chemotherapy compounding by manual pharmacists. Currently, robotic systems are widely employed in several countries and have begun to be introduced in Thailand. This systematic review and meta-analysis aim to evaluate the preparation errors and contamination rates associated with intravenous chemotherapy compounding, comparing robotic systems with manual preparation by clinical oncology pharmacists. A total of 2,197 studies were initially identified from various databases, including PubMed, ScienceDirect, Cochrane reviews, and others, covering publications from database inception through April 16, 2025. Of these, 11 studies were selected for inclusion. The quality of the included studies was assessed using the ROBINS-I tool, revealing that 7 studies had a moderate risk of bias, while 4 studies had a serious risk of bias. The meta-analysis demonstrated that robotic chemotherapy compounding was not significantly associated with lower rates of absolute dose errors (MD=-0.04, 95%CI -0.40, 0.33, I2=99.7% model with random effect model), external contamination (OR=0.49, 95%Cl 0.10, 2.40, I2=71.4% model with random effect model) and with a reduction in failure rates or rejected dose (OR=0.45, 95%Cl 0.09, 2.17, I2=84.1% model with random effect model). Additionally, environmental contamination (OR=1.61, 95%Cl 0.72, 3.63, I2=54.3% model with random effect model) was more frequently observed in the robotic compounding group, although this difference was not statistically significant. In conclusion, robotic chemotherapy compounding represents an effective alternative to manual preparation by pharmacists. However, its high cost should be considered, and implementation must align with each hospital’s specific needs and financial capabilities.